Atomic force microscopy imaging of classical and nonclassical surface growth dynamics of calcium orthophosphates - Li, M.; Wang, L.; Putnis, Christine (The Royal Society of Chemistry, 2018)
© 2018 The Royal Society of Chemistry. Calcium orthophosphates (Ca-Ps) have long been the focus of extensive research due to their significance as inorganic phases of biomineral bones and teeth and the primary constituent of the majority of pathological calcified tissues. The utilization of atomic force microscopy (AFM) as an in situ imaging technique is to probe nanoscale and even near-molecular processes during Ca-P crystallization and unravel the underlying modulation mechanisms of biological molecules. According to the solubility defined as the equilibrium solute concentration for Ca-P growth, we first review classical crystallization mechanisms of brushite (DCPD) and the role of step-specific interactions, providing a context for interpreting the changes of step movement velocities and visualizing the modification of the growth hillock (spiral growth) morphology and the step features on a DCPD crystal surface in the presence of growth modulators using AFM. A nonclassical crystallization pathway for octacalcium phosphate (OCP) and hydroxyapatite (HAP) is then reviewed so that the effects of biomolecules, such as amelogenin proteins on tooth enamel formation, are set in a broader biomineralization context. Finally, we show how recent advances using AFM-based single molecule force spectroscopy (SMFS) have provided the energetic basis for probing the interactions between osteopontin (OPN) peptides and HAP to define a thermodynamic understanding of OPN roles in the growth of HAP at biomimetic cell membrane surfaces. These in situ AFM observations improve the fundamental understanding of the interfacial growth of Ca-P biominerals and their biomimetic substitute materials.